Integrasi Environmental Education Pada Pembelajaran Matematika Sebagai Mitigasi Ancaman Perubahan Iklim - Zahra Nugraheni (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
The climate change that occur on earth is very urgent to be searched for efforts of disaster mitigation. Education, especially mathematics education, has a strategic role in introducing and preventing climate change in the next generation. The reason is, mathematics is the mother of all sciences which is closely related to all aspects of life and is also the basis for technological development. Efforts to mitigate the threat of climate change in the school environment are through the integration of environmental education in the school curriculum, especially in mathematics learning process. This research is a literature review research related to the integration of environmental education in mathematics learning. It is hoped that the results of this research can become a reference for teachers as the efforts to mitigate climate change through integrating environmental education in mathematics learning.